2014
DOI: 10.1038/nature13568
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the human gut microbiome in liver cirrhosis

Abstract: Liver cirrhosis occurs as a consequence of many chronic liver diseases that are prevalent worldwide. Here we characterize the gut microbiome in liver cirrhosis by comparing 98 patients and 83 healthy control individuals. We build a reference gene set for the cohort containing 2.69 million genes, 36.1% of which are novel. Quantitative metagenomics reveals 75,245 genes that differ in abundance between the patients and healthy individuals (false discovery rate < 0.0001) and can be grouped into 66 clusters represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

101
1,734
11
19

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,799 publications
(1,865 citation statements)
references
References 53 publications
101
1,734
11
19
Order By: Relevance
“…Case-control studies have associated microbial traits in individuals with patterns of diseases, thereby implicating gastrointestinal microbial communities in a range of human disorders [6][7][8][9][10] . Metagenomics is able to resolve differences in the functional potential of microbial communities and has revealed a surprisingly stable set of core functions, even though gastrointestinal community structures display great inter-individual variation 2 .…”
mentioning
confidence: 99%
“…Case-control studies have associated microbial traits in individuals with patterns of diseases, thereby implicating gastrointestinal microbial communities in a range of human disorders [6][7][8][9][10] . Metagenomics is able to resolve differences in the functional potential of microbial communities and has revealed a surprisingly stable set of core functions, even though gastrointestinal community structures display great inter-individual variation 2 .…”
mentioning
confidence: 99%
“…Sequencing of DNA extracted from patient samples is the most commonly used approach for studying the human microbiome (2). Human cohort sequencing studies have found strong correlations between changes in bacterial populations and human pathophysiology (3)(4)(5)(6)(7). Mouse models have been used to show that native bacterial ecology is necessary for normal physiologic functions and dysbiosis causes diseases like obesity, cancer, diabetes, and colitis among others (8)(9)(10)(11).…”
mentioning
confidence: 99%
“…A 2014 study noted that patients with cirrhosis and hepatic encephalopathy were demonstrated to have relatively reduced abundance of native taxa including Lachnospiraceae, Ruminococcaceae, and a Clostridial strain while having a relatively higher abundance of others such as Enterobacteriaceae and higher proportion of Firmicutes (5). Multiple studies have demonstrated this same trend across cirrhotics due to alcohol, HCV, and cryptogenic etiologies (6)(7)(8)(9). The ratio of native versus non-native bacterial strains in cirrhotic patients is referred to as cirrhosis dysbiosis ratio (CDR).…”
Section: Microbiome Alterations In Cirrhosismentioning
confidence: 91%